Massive MIMO systems with low-resolution ADCs: Baseband energy consumption vs. Symbol detection performance - Moon, Seungsik; Kim, In Soo; Kam, Dongyun; Jee, Dong Woo; Choi, Junil; Lee, Youngjoo (IEEE Access, 2019)
In massive multiple-input multiple-output (MIMO) systems using a large number of antennas, it would be difficult to connect high-resolution analog-to-digital converters (ADCs) to each antenna component due to high cost and energy consumption problems. To resolve these issues, there has been much work on implementing symbol detectors and channel estimators using low-resolution ADCs for massive MIMO systems. Although it is intuitively true that using low-resolution ADCs makes it possible to save a large amount of energy consumption in massive MIMO systems, the relationship between energy consumption using low-resolution ADCs and detection performance has not been properly analyzed yet. In this paper, the tradeoff between different detectors and total baseband energy consumption including flexible ADCs is thoroughly analyzed taking the optimal fixed-point operations performed during the detection processes into account. In order to minimize the energy consumption for the given channel condition, the proposed scheme selects the best mode among various processing options while supporting the target frame error rate. The numerous case studies reveal that the proposed work remarkably saves the energy consumption of the massive MIMO processing compared with the existing schemes.
Keywords: Analog to digital converters; Channel conditions; Detection performance; Energy consumption problems; Fixed point operation; Low resolution; Massive multiple-input- multiple-output system (MIMO); Symbol detection; energy consumption; low-resolution ADCs; Massive MIMO; symbol detection